Nigeria's Public Accountability and Supreme Audit Institutions: A Case Study of Lagos State Civil Service - Iredele, Oluwamayowa Olalekan; Olanrewaju, Shadeko Oladele (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The study investigates the role of auditors from the Office of Internal Audit in enhancing financial performance and accountability within Lagos State Civil Service. Financial accountability is crucial for transparency, integrity, and responsible management of funds. However, inadequate audit resources, resistance to scrutiny, inefficiencies in audit processes, and non-regulatory compliance can affect it. The study aims to evaluate the impact of financial audits conducted by the Office of Internal Audit on the financial accountability of Ministries, Departments, and Agencies in Lagos State. The research employs an explanatory research design to assess cause-effect relationships using numerical data and statistical analysis. Primary data was gathered through structured questionnaires targeting auditors, financial officers, and administrators within Ministries, Departments, and Agencies (MDAs). The collected data was analyzed using regression analysis, correlation tests, and descriptive statistics to establish relationships between variables. At 0.05 significant level, the study's key findings of the study revealed that financial, performance, and regulatory audits significantly improve financial accountability among MDAs in Lagos State, fostering transparency, responsible resource management, and ethical governance. The study however concludes that regular financial audits are essential for accountability, policy decisions, and strengthening internal controls. Performance audits guide resource allocation, budget planning, and enhance financial oversight. Regulatory and compliance audits ensure ethical governance, legal compliance, and safeguard public resources against mismanagement and corruption. The study recommends that regular implementation of financial audits to maintain accountability and guide policy decisions. Strengthening internal controls and audit committees is crucial for sustained financial discipline.